Epidermoid Cysts after Percutaneous Needle Fasciotomy for Dupuytren Contracture: Literature Review - Breidung, David; Delavari, Sarina; Megas, Ioannis Fivos; Billner, Moritz; Reichert, Bert (Plastic and Reconstructive Surgery Global Open, 2024)
This case report presents a rare complication after percutaneous needle fasciotomy for Dupuytren contracture: the development of epidermoid cysts. A 60-year-old man who had previously undergone a needle fasciotomy required a subsequent limited fasciectomy due to disease progression. Unexpectedly, epidermoid cysts were discovered during the procedure. The successful removal of the cysts, together with the removal of the contracture cord, resulted in a good functional outcome. The conducted literature review identified four case reports of epidermoid or dermoid cysts after treatment for Dupuytren contracture. The reported cases in the literature and our case emphasize the need for adaptability in the management of Dupuytren contracture and the potential for unexpected complications. Further investigation is essential to understand the relationship between Dupuytren disease and cyst formation.
CRIS-Team Scopus Importer:2024-05-17